The Relationship of Religious Involvement Indicators and Social Support to Current and Past Suicidality among Depressed Older Adults - Rushing, Nicole C. (2012)
OBJECTIVES: Elderly people, particularly those with major depression, are at the highest risk for suicide than any other age group. Religious involvement is associated with a range of health outcomes including lower odds of death by suicide. However, not much is known about the effects of religious involvement on suicidal ideation in the elderly or which aspects of religiosity are beneficial. The current study examined the relative influence of various conceptualizations of religious involvement, above and beyond the protective effects of social support, on current and past suicidality among depressed older adults. METHOD: Participants were 248 depressed patients 59 years and older enrolled in the Neurocognitive Outcomes of Depression in the Elderly (NCODE) study. A psychiatrist assessed current suicidal ideation using the suicidal thoughts item from the Montgomery-Asberg depression rating scale (MADRS). Past history of suicide attempts, four religious involvement indicators, social support indicators, and control variables were assessed via self-report. RESULTS: Church attendance, above and beyond importance of religion, private religious practices and social support, was associated with less suicidal ideation; perceived social support partially mediated this relationship. Current religious practices were not predictive of retrospective reports of past suicide attempts. CONCLUSION: Church attendance, rather than other religious involvement indicators, has the strongest relationship to current suicidal ideation. Clinicians should consider public religious activity patterns and perceived social support when assessing for other known risk and protective factors for suicide and in developing treatment plans.